FAMILY LIFE AND PEER INFLUENCE AS CORRELATES OF ACADEMIC ADJUSTMENT OF STUDENTS WITH VISUAL IMPAIRMENT IN OYO STATE, NIGERIA - Sunday Abimbola Abodunrin; Mercy O. Enweremadu; Assam Andy Edim (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2024)
This paper examines family life and peer influence as correlates of academic adjustment of students with visual impaired. The purpose of the study is to identify the relationship, joint contribution and relative contribution of family life and peer influence to academic adjustment of students with visual impairment. The findings show that, family life and peer influence has significant impact on the academic adjustment of students with visual impairment. The study recommends that, parents should ensure that all necessary support needed by their children with visual impairment must be taking care of so as to help them in their academic pursuit coupled with positive peer influence.